The role of corporate posture as moderation of relationships among the antecedents of sustainability reporting disclosure in Indonesia - Sofwan Farisyi (Cogent Business & Management, 2023)
AbstractThe purpose of this study is to compare companies that do not and carry out social and environmental responsibility on the vision and mission of the company (Corporate Posture) on the determinants of Sustainability Reporting Disclosure. This study is a quantitative study, using secondary data taken from the annual reports of 113 public companies on the Indonesia Stock Exchange that provide financial reports and sustainability reporting from 2013 to 2020. There were 14 companies that did not have a Corporate Posture (Group 1) and 99 companies that did have a Corporate Posture (Group 2). Data analysis uses a multigroup structural equation model. Based on the results in Group 1 and Group 2, it was found that Corporate Posture proved to be a moderator in strengthening the relationship between Ownership Structure, Board Qualification & Experience, and Sustainability Reporting Regulations on Sustainability Reporting Disclosures. On the other hand, based on the results of this study, it was found that Corporate Posture does not affect Firm-size on Sustainability Reporting Disclosures. The role of Corporate Posture is a moderation of the relationship between Firm Size, Ownership Structure, Board Qualification & Experience, and Sustainability Reporting Regulations on disclosure of sustainability reporting.